2016
DOI: 10.1007/978-3-319-42147-6_20
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Information Literacy in Secondary Education: How to Design Professional Development for Teachers?

Abstract: The networked information and media society provides us increasingly with digital information and knowledge. However, the effective and efficient use of information also requires a high level of information literacy (IL), the competent handling of information and the ability to do that from an early age. Despite this early beginning, the development of IL is considered an important goal of schoolteachers who are required to integrate IL into their daily teaching practice. One reason that IL has only been consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As a result, it's understandable that the students agreed with the statements, because pedagogical content knowledge is an instructive pedagogical method for teachers to plan, organize and present scientific content to students. The PKC addresses teaching knowledge in connection to the activity of teaching material, boosting student learning, through non-specific teaching techniques and approaches (SEUFERT et al, 2016). Thus, it is known that little or practically nothing has changed in distant teaching activities, gaining agreement of the subjects in connection to the statements, in reference to the didactic approach for the teacher to present content, as well as their scientific mastery over it.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it's understandable that the students agreed with the statements, because pedagogical content knowledge is an instructive pedagogical method for teachers to plan, organize and present scientific content to students. The PKC addresses teaching knowledge in connection to the activity of teaching material, boosting student learning, through non-specific teaching techniques and approaches (SEUFERT et al, 2016). Thus, it is known that little or practically nothing has changed in distant teaching activities, gaining agreement of the subjects in connection to the statements, in reference to the didactic approach for the teacher to present content, as well as their scientific mastery over it.…”
Section: Resultsmentioning
confidence: 99%
“…A joint project of the American Library Association and the American Sociological Association aimed to outline how to integrate IL standards into assignments for students of social science, particularly sociology majors (Caravello et al, 2008). Seufert et al (2016) published a model for the conceptualization and measurement of IL in education sciences, focusing on secondary education. The IL training for students at Cardiff Law School aims to develop legal analysis and reasoning skills, legal research skills and legal presentation skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies by Yu, Abrizah and Sani (2016), Majid, Chang and Foo (2016) and Seufert et al (2016) focused on the teacher's conceptualization of IL and their understanding of IL practices. Majid, Chang and Foo (2016) highlighted the need for developing a roadmap for providing IL skills at different grade levels and in different subject areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Majid, Chang and Foo (2016) highlighted the need for developing a roadmap for providing IL skills at different grade levels and in different subject areas. Seufert et al (2016) concluded that developing a learning-conducive school culture can be regarded today as one of the key challenges for the successful implementation of educational innovation and continuous quality improvement processes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation